Review of the genus Scolopostethus Fieber, 1860 (Hemiptera: Heteroptera: Rhyparochromidae) from Central Asia with description of a new species - Neimorovets, Vladimir V. (Zootaxa, 2024)
Prior to this study, five species of the genus Scolopostethus Fieber, 1860 were documented from Central Asia. Thorough examination of the collection retained at the Zoological Institute of the Russian Academy of Sciences (St. Petersburg), resulted in the description of a new species from this region, S. ferganensis sp. n. Earlier distributional records of S. affinis (Schilling, 1829) from Central Asia were demonstrated to be the result of misidentifications. An illustrated key, diagnoses, and data on distribution are provided for all five species of the genus Scolopostethus found in Central Asia.